Anti-contactin-1 autoimmune nodopathy with thymoma: case report and literature review - Tashiro, Takumi; Ogata, Hidenori; Kuwahara, Motoi; Nishijima, Haruo; Nogami, Kenichiro; Yamaguchi, Takahiro; Hayashida, Hitoshi; Maimaitijiang, Guzailiayi; Yamasaki, Ryo; Kira, Jun-ichi; Nagai, Yoshitaka; Isobe, Noriko (Frontiers in Immunology, 2025)
BackgroundsAutoimmune nodopathies (ANs) with autoantibodies against cell adhesion molecules including contactin-1 (CNTN1) located in the nodes of Ranvier and paranodes have specific clinical features. Patients with anti-CNTN1 AN accompanied by paraneoplastic status have been reported. Here, we describe three patients with anti-CNTN1 AN and concurrent thymoma. In addition, we performed a literature review to investigate the relationship between demyelinating peripheral neuropathy and thymoma.MethodsSerum CNTN1-IgG and IgG subclasses were measured by cell-based assay or enzyme-linked immunosorbent assay. Clinical, electrophysiological, and pathological data were obtained from the medical records of patients. CNTN1-IgG titers and serum neurofilament light chain (sNfL) were followed over the disease course. Through a literature survey of demyelinating peripheral neuropathy and thymoma, we summarized the clinical features and involvement of CNTN1-IgG.ResultsThree patients with CNTN1-IgG4 were elderly men, who presented with subacute disease progression, sensory ataxia, very high cerebrospinal fluid (CSF) protein levels, and apparent conduction delay in nerve conduction studies. In two patients with type B3 thymoma, thymectomy did not improve their neurological symptoms. In one case with type AB thymoma, nephrotic syndrome and pemphigus foliaceus appeared with the deterioration of neuropathy after thymectomy. All patients responded well to immunotherapies in parallel with decreased antibody titers and sNfL levels. Our literature survey identified a total of twelve cases, including our patients, of demyelinating peripheral neuropathy with thymoma. Ten were male and the mean age at onset was 57 years. Limb weakness and sensory ataxia were observed in 73% and 71% of patients, respectively. CSF protein levels were elevated in seven of nine patients. Four patients with Good’s syndrome or malignant thymoma progressed to death, whereas the other patients had a favorable response to mono- or combined immunotherapies. CNTN1-IgG was identified in four patients including those in this report.ConclusionThymoma can be accompanied by anti-CNTN1 AN. Adequate immunotherapies should be considered regardless of the efficacy of thymectomy.